Capsule endoscopy in Crohn's disease surveillance: A monocentric, retrospective analysis in Italy - Calabrese, Carlo; Gelli, Dania; Rizzello, Fernando; Gionchetti, Paolo; Torrejon Torres, Rafael; Saunders, Rhodri; Davis, Jason (Frontiers in Medical Technology, 2022)
Background Crohn's disease (CD) is a potentially debilitating condition that burdens Italian healthcare substantially. The symptomatic management relies on prompt therapy adjustment to reduce flares and follow-up diagnostic inputs to maximise remission. Capsule endoscopy (CE) has introduced advantages in CD diagnostics, allowing the direct inspection of the entire gastrointestinal mucosa. The diagnostic procedure is comparable in effort to standard ileocolonoscopy (IC) but requires no anaesthesia. Whether CE follow-up improves clinical outcomes remains to be defined. Objectives To provide a preliminary evaluation of CE in terms of clinical outcomes with respect to the standard of care ileocolonoscopy/MRE in Italy. Methods This retrospective analysis utilises anonymised, monocentric data from the S. Orsola-Malpighi Hospital IBD database in Bologna, Italy, collected between 1999 and 2019. Out of 421 adult patient records, 100 were included in the analysis (50 per arm, matched per demographic and clinical characteristics). The CE represented the intervention arm, whereas ileocolonoscopy/magnetic resonance enterography was the standard of care. The use of biologics, symptomatology course, and surgery were the outcomes. Results The two techniques performed similarly overall. In general, no significant difference emerged in the use of biologics. The use of biologics appears reduced in the CE group, only in L4 patients after the first follow-up year. Similarly, surgery was seemingly less frequent among L4 patients in the CE group. No difference was found between groups in flare occurrence and duration. CE patients might have experienced longer and earlier first remissions, but no long-term difference persisted. Conclusions The CE group showed an apparent reduction in biologics and surgery, limiting to L4 diagnoses. More extensive, prospective, multicentre, randomised studies must corroborate these preliminary findings.